An Analytical Study of the Epistle of Shaykh Ibrāhīm Niyās al-Kawlakhi - Zubair Muhammad Isa (IJAS: International Journal of Arabic Studies, 2026)
This study presents an analytical examination of one of the prose epistles of Shaykh al-Ḥājj Ibrāhīm Niyās al-Kawlakhi, focusing on its literary, rhetorical, and spiritual dimensions. The paper explores the stylistic characteristics of the epistle, including its diction, imagery, sentence structure, and use of Sufi terminology, situating it within the broader tradition of Arabic Islamic prose. Particular attention is given to the author’s rhetorical strategies, such as restriction, exhortation, and symbolic expression, which reflect his deep spiritual insight and literary competence. The study also highlights the thematic concerns of the epistle, especially sincerity in worship, adherence to religious discipline, concealment of spiritual secrets, and rejection of ostentation in mystical practice. Using a descriptive and analytical approach, the paper demonstrates that the epistle represents a refined model of West African Sufi prose that balances aesthetic elegance with doctrinal authenticity. The findings confirm Shaykh Ibrāhīm Niyās’s significant contribution to Arabic Sufi literature and Islamic intellectual history in West Africa.